Vascular Manifestations of COVID-19 – Thromboembolism and Microvascular Dysfunction - Roberts, Kirsty A.; Colley, Liam; Agbaedeng, Thomas A.; Ellison-Hughes, Georgina M.; Ross, Mark D. (Frontiers in Cardiovascular Medicine, 2020)
The coronavirus pandemic has reportedly infected over 22 million individuals and caused over 778,000 deaths worldwide. This novel coronavirus, officially named severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), although primarily causes significant respiratory distress, can have significant deleterious effects on the cardiovascular system. Severe cases of the virus frequently result in respiratory distress requiring mechanical ventilation, often seen, but not confined to, individuals with pre-existing hypertension and cardiovascular disease, potentially due to the fact that the virus can enter the circulation via the lung alveoli. Here the virus can directly infect vascular tissues, via TMPRSS2 spike glycoprotein priming, thereby facilitating ACE-2-mediated viral entry. Clinical manifestations, such as vasculitis, have been detected in a number of vascular beds (e.g. lungs, heart, and kidneys), with thromboembolism being observed in patients suffering from severe coronavirus disease (COVID-19), suggesting the virus perturbs the vasculature, leading to vascular dysfunction. Activation of endothelial cells via the immune-mediated inflammatory response and viral infection of either endothelial cells or cells involved in endothelial homeostasis, are some of the multifaceted mechanisms potentially involved in the pathogenesis of vascular dysfunction within COVID-19 patients. In this review, we examine the evidence of vascular manifestations of SARS-CoV-2, the potential mechanism(s) of entry into vascular tissue and the contribution of endothelial cell dysfunction and cellular crosstalk in this vascular tropism of SARS-CoV-2. Moreover, we discuss the current evidence on hypercoagulability and how it relates to increased microvascular thromboembolic complications in COVID-19.